Association between Hotel Employees’ Sociodemographic Characteristics and Employee Place Identity: Preliminary Findings from Nakuru Town, Kenya (African Multidisciplinary Journal of Research, 2022)
Over the last few years, there have been concerns about rapid urbanization caused by the proliferation of hotels, which in turn poses a huge threat on sustainability in the hospitality industry. Urban planners postulate that hotel employees’ sense of place is critical to the sustainability of hotels, with implications on the overall urban sustainability; however, there is paucity of research that has investigated this phenomenon amongst hotel employees in Kenya, especially in Nakuru County. This research paper informed by place identity theory, presents preliminary findings on sociodemographic characteristics associated with employee place identity in selected hotels in Nakuru town. The study used cross-sectional survey to collect data from 16 hotel employees. Data were collected using a questionnaire with closed ended questions. Place identity was operationalized using validated urban-related Identity measures. Place identify is a multidimensional construct which comprises employee's external evaluation, general attachment, continuity with personal past, perception of familiarity, and commitment. Descriptive statistics were used to summarize data from the sample. Association between sociodemographic characteristics associated with employee place identity were assessed using Chi-Square tests. An independent T-Test was conducted to examine statistically significant differences on employee place identity by gender. The mean for males was 3.17 (SD = 0.73), while the mean for females was 3.50 (SD = 0.56). Although females had a higher value for place identity compared to males, the differences were not statistically significant (t = -.98, p = 0.14). The mean for employees aged 30 years and below was 2.80 (SD = .64), while the mean for employees aged 31 years or older were 3.50 (SD = 0.58). Differences in employee place identify by age were statistically significant t = -2.25, p = 0.04). Differences in employee place identify by highest level education attained were statistically significant, t = -3.01, p = 0.01). These findings have implications that employers who recognize employees who have attained higher education level, contribute positively towards their demonstration of greater stewardship towards environmental conservation.Keywords: Sustainable development; sustainable hospitality, hotels, place identity; Nakuru town, Kenya